Seroprevalence of Brucellosis in Sheep in the Gaibandha District of Bangladesh (Progressive Agriculture, 2013)
Brucellosis is an important zoonoses causing signififant economic loss but is very often neglected in Bangladesh. Therefore, a survey was undertaken to investigate the seroprevalence of brucellosis in sheep of selected areas (Gaibandha sadar and Gobindagonj upazilas) in the Gaibandha districts of Bangladesh. A total of 206 sera samples were collected from sheep and were tested for presence of Brucella specific antibody by Rose Bengal Plate Test (RBPT) as screening test and the RBPT positive samples were further confirmed using indirect Enzyme-linked immunosorbent assay (i-ELISA). Information of sheep's age, sex, housing system, pregnancy status, abortion and reproductive disorder were collected using questionnaire. The overall seroprevalence of brucellosis in sheep was recorded as 3.39% in RBPT and 2.91% in i-ELISA. The prevalence of brucellosis in female sheep (3.41%) was higher than male (3.33%). The prevalence of brucellosis in sheep with abortion history was higher (4.34%) than the sheep with no abortion (3.08%). The highest prevalence of brucellosis (4.00%) was found in sheep keeping with others species such as cattle and goat compared to the sheep keeping alone (1.79%). The higher rate (4.59%) of Brucella antibody was recorded in sheep of 1-2 years of age. Brucellosis might be an important hinders for sheep production in Bangladesh. The present study will help to develop an appropriate prevention strategy for brucellosis in Bangladesh.DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16562Progress. Agric. 23(1 & 2): 25 32, 2012